E-learning in Saudi Arabia: Past, present and future - Ali Mohammad Al-Asmari (19811418) (2014)
The emergence of information and instructional technologies and their influence on teaching and learning has brought about significant changes in academic environment in the Kingdom of Saudi Arabia (KSA). The new learning trend has made it mandatory to equip teachers in educational institutions with the necessary skills to cope with the new challenges. The urgent need for e-learning in KSA has resulted from the massive population growth vis-à-vis the scarcity of teachers in both quantity and quality, including the need to reduce financial burden. Since 2002, when e-learning started in KSA, it has gained recognition and interest among academic institutions, academics and students, though with a relatively slow pace. This paper takes into account the growth of e-learning in KSA. It analyzes the potential need and the overall impacts of e-learning on various stakeholders. The paper also discusses the current e-learning developments as well as future prospect. Other Information Published in: Near and Middle Eastern Journal of Research in Education, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/nmejre.2014.2